2008
DOI: 10.1590/s0102-86502008000700006
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory renal growth and mitochondrial function: the influence of warm ischemia and reperfusion

Abstract: PURPOSE: To evaluate the influence of ischemia/reperfusion injury on renal compensatory growth (CGR) and mitochondrial function. METHODS: Forty five Wistar rats were divided in 3 groups: Control Group (GC) - 21 rats were submitted to a sham laparotomy and sacrificed at 1st (6 rats) and 7th (15 rats) postoperative days to evaluate the dry weight of both kidneys and their growth during 1 week (6 rats) and to quantify mitochondrial respiration (9 rats); Group 1 (G1) - 12 rats underwent right nephrectomy and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Macroscopically, at 8 days, in all the groups, the size of the obstructed kidney was found to be slightly increased compared with that of the contralateral kidney. Tucci-Junior et al 10 demonstrated that this increase in size is due to increased mitochondrial respiration activity as a compensatory mechanism of the ischemic organ.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macroscopically, at 8 days, in all the groups, the size of the obstructed kidney was found to be slightly increased compared with that of the contralateral kidney. Tucci-Junior et al 10 demonstrated that this increase in size is due to increased mitochondrial respiration activity as a compensatory mechanism of the ischemic organ.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Two-dimensional and color Doppler ultrasound examinations were performed in 16 randomly selected animals at 7 days before the surgical procedure to determine patterns of normality of the structural organ and hemodynamics using an ultrasound equipment (GE Logiq-E) with sector transducer 8C (4)(5)(6)(7)(8)(9)(10)(11). In these animals, color Doppler ultrasound was also performed after the placement and removal of the vascular clip, allowing the assessment of renal ischemia and reperfusion.…”
Section: Assessment Using Two-dimensional and Color Doppler Ultrasoundmentioning
confidence: 99%
“…Additionally, compensatory renal hypertrophy, a phenomenon already well established in the literature may have occurred 24 .…”
Section: Introductionmentioning
confidence: 85%
“…A protective effect has also been observed with the use of verapamil 3 . However, no variation in ATP production was observed in the analysis of mitochondrial function of rat kidneys obtained during the development of compensatory renal hypertrophy (which causes an increased renal blood flow) followed by ischemia and reperfusion 4 .…”
Section: Introductionmentioning
confidence: 95%